KANDUNGAN NILAI HISTORIS DALAM NOVEL GLONGGONG KARYA JUNAEDI SETIYONO: KAJIAN SOSIOLOGI SASTRA - Muhammad Wahyu Widodo; Sri Wahyuningtyas (CARAKA, 2017)
This study aims to describe (1) figure and characterization in the novel of â€œGlonggongâ€, (2) setting in the novel of â€œGlonggongâ€, (3) historical value content in the novel of â€œGlonggongâ€. This study is a qualitative descriptive research. Data used in the form of a paragraph that contains the unit of events regarding the content of historical value. Sources of data in the form of â€œGlonggongâ€ novel by Junaedi Setiyono. The instrument of this study is the researchers themselves armed with a set of science concepts related to the problems examined. Data collection techniques using observation, reading techniques, and technical notes. The data analysis technique used is descriptive qualitative which focuses on figure and characterization, setting, and historical value content in â€œGlonggongâ€ novel by Junaedi Setiyono. Results of this study as follows. (1) character and characterization in the novel of â€œGlonggongâ€ consist of the main character, namely Glonggong who have good character, brave, modest, humble, honest, and full fidelity. Additional characters are (a) Endang, Glonggong lover who has a good character, sincere, humble, polite, and friendly like most princess of Java, (b) Suta, Glonggong good friend who has a strong character, loyal, honest, mature, and wise in making decisions, (c) Surya , has the character of an arrogant, snobby, selfish, but good-hearted and often help figure Glonggong, (d) Prayitna, has the character of a cruel, evil, arrogant, vindictive, and not to be outdone, (e)Kiai Ngali, has a good character, patient, and wise. (2) Setting in â€œGlonggongâ€ novel by Junaedi Setiyono, as follows. (a) setting time occurs at the beginning of the 19th century circa 1815-1855 when the Dutch colonial era, (b) setting places in Yogyakarta, including: Ndalem Suwandan, Puri Pringgawinatan, Tegalreja, in Semarang covers an area Srondol, and in Magelang include Residency building of Magelang, (c) social setting that the Java community life in the Dutch colonial period especially when going to and after the outbreak of war Dipanegara. (3) Historical value content that can be viewed using the social sciences in the novel of â€œGlonggongâ€among others the attitude and inflammatory spirit of nobles and commoners during the colonial era, a wide variety of properties or the original character of a handful of nobles who eventually come to the surface, and the values of the people who are very loyal struggle in maintaining national pride when will the outbreak of war Dipanegara.